Retranslation as a social activity: the case of Chinese literary canon Xi You Ji - Ruolin, Tong (Penerbit Universiti Kebangsaan Malaysia, 2025)
Xi You Ji is a popular Chinese canon and has been successfully introduced to the English-speaking world. This study sets out to carry out a comparative study of XYJ’s retranslations by Helen M. Hayes in 1930, Anthony C. Yu in 2006, and Julia Lovell in 2021. This study is tethered to narrative theory and paratextual analysis. By comparing the narratives encoded in the paratexts, this study aims to identify how paratexts function in reframing the narratives of XYJ. Specifically, this paper adopts the narrative framing strategies proposed by Baker (2006) to analyse the narratives elaborated in the paratexts. This paper shows that the three abridgements are all in accordance with the storyline of the source text, while there are obvious differences regarding genre and theme among these versions. Accordingly, Hayes reframed the fiction as a spiritual fable of a historical monk’s journey to India with Mahayana Buddhist interpretation, Yu a serious allegory highlighting karma and redemption of Monkey and Sanzang, and Lovell a popular folklore of Monkey fused with religious, historical, and sarcastic elements. Moreover, the three versions enlarge the scope of the original narrative to the Anglophone setting by publicising the Chinese fantasy with a story of Buddhist scripture-obtaining. This study provides the theoretical basis and a new paradigm for further research on narrative reframing and hopes to offer insights into the overseas promotion of Chinese literature.